PENERAPAN KONSELING KELOMPOK UNTUK MENINGKATKAN KETERAMPILAN SOSIAL EMOSIONAL PADA REMAJA AWAL - Ari Prasetyoaji; Dian Sugiarti; Desta Bagus Prasetya; Dwi Suryanti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study was motivated by the phenomenon of low social-emotional skills among early adolescent students, which is indicated by difficulties in managing emotions, conflicts with peers, and impulsive behavior in social interactions. These conditions indicate the need for guidance and counseling services that can help students improve their social and emotional maturity. The purpose of this study was to examine the effectiveness of implementing group counseling using the Gestalt approach in improving students’ social-emotional skills. This study employed a quantitative approach with an experimental method using a Posttest Only Control Group Design, involving an experimental group that received treatment and a control group as a comparison that did not receive treatment. The research subjects were selected using a purposive sampling technique from students who had low social-emotional skill scores and were indicated to have unfinished business. Data was collected using a social-emotional skills questionnaire and analyzed using a T-test. The results showed a significant difference between students who received the treatment and those who did not receive the treatment, indicating that group counseling using the Gestalt approach is effective in improving social-emotional skills among early adolescents